Consumption of Water for Household Needs and the Affecting Factors at Banyudono Boyolali - Anna, Alif Noor; Kaeksi, Retno Woro; Priyana, Yuli (Forum Geografi, 2000)
The consumption of drinking water for a community is different from one area to the other. This is normally influenced by the population development, socio-economic, cultural, and physical conditions mainly related to the supply of drinking water and how to exploit it. Banyudono district is an area located in the regency of Boyolali. The development of this area depends on Boyolali City and Kartasura district. Such a location enables the area to have a process of the physical and socio-economi developments. In addition, it has an influence upon social behaviour to consume water. This research is aimed at knowing the average consumption of household need and analyzing the factors influencing the utilization of water as drinking water. The result of this research indicated that 1) the average consumption of a human being for drinking water was 79,37 litter a day. It means that the onsumption of a human being for drinking ater generally ranged from 60 to 80 litter a day; 2) most of the ater was consumed to meet basic needs such as cooking, drinking, bathing, and washing; 3) the difference of the average consumption was influenced by the kind of water source and how to exploit it; 4) a parameter of the most significant socio-economic condition that took effect on the average consumption for drinking water was the parameter of income with correlation of 0.362 and the significant level of 0.01.